Perbandingan Pengalaman Keberagamaan Siswa SMK Dengan SMU - Assani, Achmad Hiebran (Jurnal Tarbiyatuna, 2019)
Educational institutions have an influence in shaping the character and religiosity of students but not all educational institutions are able to change the behavior of their students. In recent years there have been many immoral cases involving students such as drugs, fighting, truant. Even educational institutions with religious backgrounds do not fully succeed in making student religiosity better. This study aims to determine the level of religious experience of vocational students with high school. The method used is a quantitative method. Subjects in this study were 120 students. The sampling technique used is simple random sampling technique. Data collection using questionnaires or questionnaires on the scale of religious experience. Then the data are analyzed using descriptive analysis and testing in hypotheses using the independent sample "T-test" test. Research findings show that; The religious experience of vocational students is included in the high category with a percentage of (88.3%) and 11.7%, the religious experience of high school students is included in the high category with a percentage of (88.3%) and 11.7%, and there is no difference in the level of religious experience in SMK students with high school students.